New insights into the functions and regulations of MAP215/MOR1 and katanin, two conserved microtubule-associated proteins in Arabidopsis. (31st December 2023) - Liu, Xiayan; Yu, Fei
ABSTRACT: Plant microtubules (MTs) form highly dynamic and distinct arrays throughout the cell cycle and are essential for cell and organ morphogenesis. A plethora of microtubule associated-proteins (MAPs), both conserved and plant-specific, ensure the dynamic response of MTs to internal and external cues. The MAP215 family MT polymerase/nucleation factor and the MT severing enzyme katanin are among the most conserved MAPs in eukaryotes. Recent studies have revealed unexpected functional and physical interactions between MICROTUBULE ORGANIZATION 1 (MOR1), the Arabidopsis homolog of MAP215, and KATANIN 1 (KTN1), the catalytic subunit of katanin. In this minireview, we provide a short overview on current understanding of the functions and regulations of MOR1 and katanin in cell morphogenesis and plant growth and development.